CAVITY FLOW CONTROL OF STEPPED HULL FOR WING-IN-GROUND CRAFT (Journal of Transport System Engineering, 2024)
A wing-in-ground (WIG) craft is a vehicle that is designed to fly at a low altitude and takes advantage of the ground effect. This helps improve the craft’s aerodynamic performance, which in turn reduces fuel consumption as well as improve its overall efficiency. However, the existence of stepped hull on WIG craft causes increase in aerodynamic drag during flight. The abrupt geometry of the stepped hull causes flow separation and reduces the craft’s aerodynamic performance. Therefore, this study aims to investigate the effect of cavity as passive flow control on the aerodynamic performance of a WIG craft with a stepped hull. The experiments were conducted in a subsonic wind tunnel at freestream velocity of 5 m/s to 30 m/s. The results show improvement of up to 7% in the lift-to-drag ratio for the current cavity configurations compared to the baseline model. This shows that the cavity is effective and has a huge potential as a passive flow control for a wing-in-ground craft with a stepped hull.
Keywords: cavity; wing-in-ground craft; passive flow control; backwards-facing step